Pierwotna dyskineza rzęsek - nowe możliwości diagnostyczne i aktualne zalecenia opieki nad pacjentem na przykładzie przypadku klinicznego - Solka, Magdalena; Grzela, Katarzyna; Sulikowska-Rowińska, Anna; Krawiec, Marta (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Primary ciliary dyskinesia (PCD) presents a diagnostic challenge. Coexistence of multiorgan abnormalities may facilitate the diagnosis. In this article, we present a case of a patient with a complex congenital heart disease and recurrent severe lower respiratory tract infections, in whom further diagnostics confirmed PCD with CCDC39 gene mutation. In recent years, genetic testing for PCD forms a valuable completion of the ciliary biopsy with electron microscopy. Once diagnosis of PCD is established, proper clinical care will have to be rendered to reduce the complications of the disease. In this article, the current recommendations for patient's clinical visits' regimen, laboratory testing and suggested prophylactic methods are presented.